Sedimentologia e proveniência de depósitos recentes do rio amazonas, entre Santarém (PA) e Macapá (AP) - LIMA JUNIOR, Walmir de Jesus Sousa (2019)
The Amazon River is the largest in the world, having the highest hydric and sediment discharge. The dispersion of sediments occurs in several kinds of sandy bedforms and accumulations of fine material in floodplains. The characterization of sandy deposits need of precise sedimentological and mineralogical analysis in order of identified the texture and heavy mineral-based provenance. These sediments were sampled in the Amazon River between Santarém (PA) and Macapá (AP). Subaqueous dunes, sandwaves and sandy bars formed by coalescence of secondary bedforms, forming shoals influenced by the swash/ backswash of waves. During the low waters of the river aeolian barchan dune and wave ripples rework the emergent bars. The analysis of particle size distribution revealed the predominance of fine sand in the samples. The sorted degree ranged generally of well sorted to very well-sorted, the kurtosis is leptokurtic and extremely leptokurtic indicating the dominance of a high energy geological agent. The asymmetry is more commonly positive to very positive, whose representative samples were there sampled in the confluences of the Tapajós and Xingu rivers with the Amazonas river, characterized by lowerest hydrodynamic. The assembly composed predominantly of zircon (14,7%), tourmaline (5,6%), staurolite (5,4%), garnet (3,8%), hornblende (22,6%), augite (22%) and hypersthene (14,8%), occurs subordinately rutile (1,9%), zoisite (2,55%), epidote (1,3%) and polymorphs of Al2SiO5 (1,57%). The ZTR maturity index revealed a tendency for values less than 10%, representing superabundance of unstable minerals. The rate of weathering provided by Est / ZTR + Est demonstrated, as expected, the opposite of ZTI index, which defines the degree of sediment reworking. The predominance of unstable heavy mineral grains associated with previous zircon ages suggest for studied sediments mainly that igneous rock of the Central Amazonia Province (2,5 Ga) were the major sources and major contributors among the geochronological provinces of the Eastern Amazonia.